Long-Pulsed Luminescence for the Measurement of Dissolved Oxygen. Issue 3 (March 2014) - Fitzgerald, Noel S.; Burgess, Lloyd W.; Yang, Jeffrey C.-Y.; Kim, Prince J.; Jang, Sei-Hum; Jen, Alex K.-Y.
Thin-film luminescent sensors were used to measure dissolved oxygen in picoliter volumes for the purpose of monitoring single-cell oxygen consumption rates, and that work served as the motivation for the development of the method described here. A few different platinum porphyrin sensor materials were examined, with all measurements conducted microscopically. By employing convolution theory to understand observed responses, including an unexpected red luminescent emission from an optic, we developed a new, rapid method for the determination of exponential decay lifetime. This new method of long-pulsed luminescence offers substantially improved signal-to-noise ratios for detected signals as long as self-illumination sources are carefully controlled in the experimental set-up.